2019
DOI: 10.1073/pnas.1908198116
|View full text |Cite
|
Sign up to set email alerts
|

A round Earth for climate models

Abstract: Sunlight drives the Earth’s weather, climate, chemistry, and biosphere. Recent efforts to improve solar heating codes in climate models focused on more accurate treatment of the absorption spectrum or fractional clouds. A mostly forgotten assumption in climate models is that of a flat Earth atmosphere. Spherical atmospheres intercept 2.5 W⋅m−2 more sunlight and heat the climate by an additional 1.5 W⋅m−2 globally. Such a systematic shift, being comparable to the radiative forcing change from preindustrial to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…The plane‐parallel assumption treats atmospheric layers as flat slabs rather than spherical shells. A spherical atmosphere intercepts 2.5 W m −2 more radiation and heats the atmosphere by 1.5 W m −2 in the global‐annual mean relative to the plane parallel atmosphere commonly used in ESMs (Prather & Hsu, 2019). This effect is especially strong in polar latitudes where solar zenith angles are larger, where our study shows spectrally resolved albedo has the greatest impact.…”
Section: Discussionmentioning
confidence: 99%
“…The plane‐parallel assumption treats atmospheric layers as flat slabs rather than spherical shells. A spherical atmosphere intercepts 2.5 W m −2 more radiation and heats the atmosphere by 1.5 W m −2 in the global‐annual mean relative to the plane parallel atmosphere commonly used in ESMs (Prather & Hsu, 2019). This effect is especially strong in polar latitudes where solar zenith angles are larger, where our study shows spectrally resolved albedo has the greatest impact.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the surface temperature has been assumed to be 15°C which is not the same as the measurement-based Es values of the Earth. Prather and Hsu [16] have found that the Earth receives 1.5 Wm -2 more insolation energy than in the climate models. This is since the Earth is a spherical object, but the climate models are based on the flat Earth model.…”
Section: Dependency Of Emitted and Absorbed Fluxesmentioning
confidence: 98%
“…The solar heating module Solar‐J (Hsu et al., 2017; hence H2017) is embedded in our chemistry‐transport model (CTM) and used to integrate climate‐relevant heating rates using the European Center's Integrated Forecast System meteorological data that drives the CTM simulation of atmospheric chemistry (M. J. Prather et al., 2017; Szépszó et al., 2019). This CTM + Solar‐J model quantified the errors related to spherical geometry of the atmosphere (M. J. Prather & Hsu, 2019; hence P2019). Here, we use that code and diagnostic framework (i.e., January average of hourly global calculations at horizontal resolution of 1.1° including water vapor and ice‐/liquid‐water clouds) for an extensive set of case studies.…”
Section: Introductionmentioning
confidence: 99%
“…This CTM + Solar-J model quantified the errors related to spherical geometry of the atmosphere (M. J. Prather & Hsu, 2019; hence P2019). Here, we use that code and diagnostic framework (i.e., January average of hourly global calculations at horizontal resolution of 1.1° including water vapor and ice-/liquid-water clouds) for an extensive set of case studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation